ENCOURAGE INNOVATIVE ACTIVITIES OF SMALL BUSINESSES: https://doi.org/10.5281/zenodo.15472311 - Ibragimova , Shokhista (Journal of Contemporary World Studies, 2025)
This article covers the problems of stimulating the innovative activities of small business entities and ways to eliminate them. The focus of small business on innovation is assessed as an important factor in diversifying the economy, increasing competitiveness and creating new jobs. The article will analyze problems in the field and put forward proposals aimed at solving them.